The ‘‘Ins’’ and ‘‘Outs’’ of Physical Activity Policy Implementation: Inadequate Capacity,Inappropriate Outcome Measures, and Insufficient Funds - Howie, Erin; Stevick, E. (Wiley-Blackwell Publishing Inc, 2014)
BACKGROUND: Despite broad public support and legislative activity, policies intended to promote physical activity in schools have not produced positive outcomes in levels of physical activity or student health. What explains the broad failure of Physical Activity Policies (PAPs)? Thus far, PAP research has used limited quantitative methods to assess PAP outcomes. New paradigms of qualitative policy implementation research can make important contributions to explaining the causes of policy failure and to the future design of more efficacious PAP legislation. METHODS :This analysis is a case study of South Carolina's 2005 Student Health and Fitness Act (SHFA). Written documents, investigators' observation and experience, and an interview with a key stakeholder were analyzed to for themes based on theoretical frameworks from education implementation research including (1) bottom-up and top-down perspectives, (2) conceptualizing policy as practice, and (3) the implementer as learner. RESULTS: “Weak policy signals” in SHFA undermined the implementation of PAP in 3 problematic areas: inadequate capacity development for implementers, inappropriate measures of implementation, and insufficient funding. CONCLUSIONS: These findings illustrate the contributions of qualitative research and establish the need for further qualitative research into PAP implementation processes. To ensure successful future physical activity policies, policymakers, and stakeholders need to consider implementation, evaluation, and funding from the beginning phases of policy development.